Determinación de los efectos toxicológicos de suelos de cultivo de banano en el desarrollo temprano de Lactuca sativa - Valenzuela León, Mathews Josué (2020)
Toxicity bioassays make a very important contribution to the prevention and remediation of environmental impacts, thanks to the help of living organisms sensitive to environmental alterations. For the development of this research work, the objective was to determine the toxicological effects of banana cultivation soils in the early development of Lactuca sativa. The study was carried out using soil samples from 30 different banana production farms in the province of El Oro, of which 15 use an agroecological production system and the remaining 15 use a conventional fumigation system with the application of synthetic agrochemicals. The concentration of trace elements (As, S, Ba, B, Cd, Co, Cu, Cr, Ni, Pb, Se, Va, and Zn) was analyzed by multiple analysis by Inductive Coupled Plasma methodology. The toxicity indices were determined. The presence of micronuclei in radicle cells was quantified as a toxicological response to the use of agrochemicals in banana plantations. Based on an analysis carried out on the current Ecuadorian environmental regulations, it was determined that, in farms of agroecological production, Cadmium, Copper, Arsenic and Cobalt, and in farms with conventional fumigation, Boron, Cadmium, Copper, Chromium, Cobalt , Arsenic, Sulfur, Nickel and Zinc; exceed the maximum permissible limits established. In addition, a greater number of treatments with low and medium toxicity was identified in the farms with conventional fumigation compared to the farms with agroecological production. Finally, it was determined that there is no presence of micronuclei in roots.